Expression of hemoglobin in rodent neurons - Schelshorn, Dominik W.; Schneider, Armin; Kuschinsky, Wolfgang; Weber, Daniela; Krüger, Carola; Dittgen, Tanjew; Bürgers, Heinrich; Sabouri Khameneh, Fatemeh; Gaßler, Nikolaus; Bach, Alfred; Maurer, Martin H. (Journal of cerebral blood flow & metabolism, 2009)
Hemoglobin is the major protein in red blood cells and transports oxygen from the lungs to oxygen-demanding tissues, like the brain. Mechanisms that facilitate the uptake of oxygen in the vertebrate brain are unknown. In invertebrates, neuronal hemoglobin serves as intracellular storage molecule for oxygen. Here, we show by immunohistochemistry that hemoglobin is specifically expressed in neurons of the cortex, hippocampus, and cerebellum of the rodent brain, but not in astrocytes and oligodendrocytes. The neuronal hemoglobin distribution is distinct from the neuroglobin expression pattern on both cellular and subcellular levels. Probing for low oxygen levels in the tissue, we provide evidence that hemoglobin α-positive cells in direct neighborhood with hemoglobin α-negative cells display a better oxygenation than their neighbors and can be sharply distinguished from those. Neuronal hemoglobin expression is upregulated by injection or transgenic overexpression of erythropoietin and is accompanied by enhanced brain oxygenation under physiologic and hypoxic conditions. Thus we provide a novel mechanism for the neuroprotective actions of erythropoietin under ischemic—hypoxic conditions. We propose that neuronal hemoglobin expression is connected to facilitated oxygen uptake in neurons, and hemoglobin might serve as oxygen capacitator molecule.